Novel mutation G324C in WNT1 mapped in a large Pakistani family with severe recessively inherited Osteogenesis Imperfecta - Kausar, Mehran (2019)
Introduction: Osteogenesis imperfecta (OI) is a clinically and genetically heterogeneous disease with skeletal fragility and variable extra-skeletal manifestations. To date several point mutations in 18 different genes causing different types of OI have been identified. Mutations in WNT1 compromise activity of the osteoblasts leading to disturbed bone mass accrual, fragility fractures and progressive skeletal abnormalities. The present study was conducted to determine the underlying genetic cause of an autosomal recessive skeletal dysplasia in a large consanguineous family from Chinute, Pakistan.Materials and methods: Blood was collected from 24 individuals of affected family along with clinical data. Homozygosity mapping was performed to confirm consanguinity. SNPs were identified, followed by whole exome and Sanger sequencing. In silico characterization of WNT1 mutation was performed using multiple platforms. Results:Nine affected family members exhibited severe bone deformities, recurrent fractures, short stature and low bone mineral density. SNP array data revealed homozygous segments > 1 Mb in length accounting for 2.1–12.7% of the genome in affected individuals and their siblings and a single 6,344,821 bp homozygous region in all affected individuals on chromosome 12q12-q13. This region includes two potential OI candidate genes WNT1 and VDR. We did whole-exome sequencing for both genes in two patients and identified a novel damaging missense mutation in exon 4 of WNT1: c.1168G > T (NM_005430) resulting in p.G324C. Sanger sequencing confirmed segregation of mutation with the disease in family.Conclusion:We report a novel mutation responsible for OI and our investigation expands the spectrum of disease-causing WNT1 mutations and the resulting OI phenotypes.